1991
DOI: 10.5980/jpnjurol1989.82.473
|View full text |Cite
|
Sign up to set email alerts
|

Management of Vesicoureteral Reflux in Patients With Neurogenic Bladder Dysfunction

Abstract: We studied 20 cases of neurogenic bladder with vesico-ureteral reflux retrospectively. Seven patients voided with Valsalva's maneuver and 12 patients were managed with clean intermittent catheterization, but one patient required permanent urinary diversion because of uncontrollable urinary tract infection. The patients were followed by intravenous pyelography, radioisotope renogram, voiding cystourethrography, determination of serum creatinine level and urodynamic study. Anti-reflux surgery was performed in 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a previous study it has been suggested to correct the primary pathology before correcting the VUR in these kinds of patients with neurogenic bladder [20]. There are effective surgical treatment alternatives for the neurogenic bladder [21].…”
Section: Bilateralmentioning
confidence: 99%
“…In a previous study it has been suggested to correct the primary pathology before correcting the VUR in these kinds of patients with neurogenic bladder [20]. There are effective surgical treatment alternatives for the neurogenic bladder [21].…”
Section: Bilateralmentioning
confidence: 99%